Spectrophotometric analysis of dental bleaching after bonding and debonding of orthodontic brackets - Dikson Claudino; Weber Adad Ricci; Heitor Marquez Honório; Renan Vaz Machry; Luiz Felipe Valandro; Ricardo Abreu da Rosa; Jefferson Ricardo Pereira (Saudi Dental Journal)
Introduction: The aim of this study was to evaluate the bleaching effect after aging simulation in teeth submitted to bonding and debonding of orthodontic brackets. Materials and methods: For this study, 90 human premolars were selected, and randomly divided into 6 groups: control, bleaching, and other 4 groups submitted to bleaching after bonding and debonding brackets using different methods. Color measurement of sample through the CIE L*a*b* system was performed in three moments: T1 – after brackets debonding, T2 – after staining cycling, and T3 – after bleaching. For evaluation of results among the components L*, a* and b*, the two criteria analysis of variance and the multiple comparison Tukey test (p < 0.05) were used. Results: Statistically significant difference was observed among the groups submitted to brackets bonding and debonding through self-conditioning adhesive system and tungsten drill, also the control and bleaching groups between the moments T1 e T2. Conclusion: Bonding and debonding brackets methods tested in this study showed influence on the sample color change, and after the tooth bleaching process, only the group without brackets previous bonding achieved the color value presented before the staining and aging of samples in the brackets absence.